Hubungan skor controlled attenuation parameter, nilai transient elastography, dan skor fibrosis-4 dengan nilai estimasi laju filtrasi glomerulus pada pasien non alcoholic fatty liver disease - Siregar, Alfi Syahrin; Sugeng, Cerelia Esher Caroline; Waleleng, Bradley Jimmy (Jurnal Kedokteran Komunitas dan Tropik, 2024)
Background: Non-Alcoholic Fatty Liver Disease (NAFLD) is one of the most common chronic liver diseases and has become a health burden throughout the world over the last two decades. Hypertension, dyslipidemia, obesity, and insulin resistance are considered risk factors for PGK that overlap with the metabolic comorbidity of NAFLD. Several studies reported that the prevalence and risk of PGK events increased significantly in NAFLD patients compared with patients without NAFLD. Aim: To determine the relationship between controlled attenuation parameter scores, transient elastography, and FIB-4 scores with eGFR values in NAFLD patients. Methods: This was an analytical study with a retrospective approach and used a cross-sectional design. The subjects were taken using consecutive sampling technique. Data collection on CAP scores, TE scores, FIB-4 scores, and eGFR was carried out by looking at the patients' medical records. In this study, the Pearson correlation statistical test was used. Result: Correlation test results between CAP scores and eGFR showed a significant positive correlation (r=0.296; p=0.031), between TE scores and eGFR showed a non-significant positive correlation (r=-0.093; p=0.509), and FIB-4 score with eGFR showed a significant negative correlation (r=-0.281; p=0.042). Conclusion: There is a significant positive correlation between the CAP score and eLFG, a non-significant positive correlation between the TE score and eGFR, and a significant negative correlation between the FIB-4 score and eGFR. Keywords: CAP score, TE score, FIB-4 score, eGFR